A Simple Wind Model for Fast Wind Farm Simulations. Issue 5 (October 2014) - Jauch, Clemens
In this article a wind model is presented that allows simulation of realistic wind speeds over the area of a wind farm. The primary propose of this model is power system simulations, where fast simulation speed is crucial, and where it is undesirable to use different tools to run a simulation. The proposed wind model combines the too simple wind models commonly used in power system simulations of wind turbines and a sophisticated wind model that represents the different wind speeds that occur across a wind turbine rotor. The result is a farm wind model for simulating the power system behaviour of a wind farm.